Elaboración de un plan de marketing para la empresa EMS TESTING - Jimenez Baldeon, Ricardo Alexander (2024)
The aim of this study is to develop a marketing plan for EMS TESTING, located in Quito Pichincha. The research employed a mixed methodological approach, combining exploratory, diagnostic, descriptive, and documentary research. This facilitated a comprehensive analysis of the company's current situation and the identification of potential marketing strategies. An intentional sample of 163 clients and managerial staff was utilized, using surveys and interviews to gather qualitative and quantitative data. The concluded marketing plan focuses on expanding its customer base and optimizing internal efficiency through strategies such as social media campaigns, paid advertisements, and participation in local fairs. The company will strengthen its presence in both urban and rural areas, optimize web content, launch Google Ads campaigns to enhance brand visibility, implement a digital document management system to streamline operations, and introduce internal communication tools and satisfaction surveys to enhance the experience for both clients and employees. With a budget of $73,210.00, EMS TESTING is well positioned to achieve its strategic goals and ensure significant growth in 2024.